“Quantity Cannot Exist without Quality”. A “Translation” of Philosophy, Economy and Politics in Gramsci’s Notebooks - Guzzone, Giuliano (International Gramsci Journal, 2024)
This article deals with the interpretation of the dialectical law of the transformation of quantity into quality given by Antonio Gramsci in his Prison Notebooks. The author argues that Gramsci is led to reconsider the relationship between quantity and quality by the need to re-examine the concept of economic “structure” and to redefine social relations in the sphere of material production in a non-reductionist way, in contrast to Bukharin. Furthermore, the author shows that Gramsci establishes a relationship of mutual immanence between quantity and quality, on the basis of the concept of “determined market” and of the assertion of the political nature of all knowledge. Finally, the author claims that this result is summarised by Gramsci in Notebook 11 when considering the first volume of Capital (instead of Engels’s Anti-Dühring) as the authentic translation and concretisation of the Hegelian law.